The influence of experience on neuromuscular control of the body when cutting at different angles - Pan, Z.; Liu, L.; Li, X.; Ma, Y. (Journal of Motor Behavior, 2023)
Cutting is an offensive technique commonly used in football and basketball to pass the opponent`s defence by changing direction quickly in running. This paper aims to investigate the effect of experience and angle on the neuromuscular control strategies of the trunk and lower limbs during cutting. Non-negative matrix factorisation and K-means were used to extract muscle synergies (muscles that are activated in parallel) of 12 subjects with cut experience and 9 subjects without experience based on the sEMG signal collected from cutting at three cut angles (45°, 90°, and 135°), which was also mapped into the spinal motor output. Uncontrolled manifold analysis was used to establish the relationship between muscle synergies and COP. This study found that experienced subjects tended to use the lower limb muscles rather than the postural muscles as stabiliser muscles compared to novices. Experienced subjects can recruit an additional set of muscle synergy to cope with large-angle cuts. In addition, experienced subjects can activate the second muscle synergy, involving the hip and ankle stabilisation muscles, in advance to improve postural stability when cutting in large-angle. Synergy index of experienced subjects dropped rapidly before the quick stop and was relatively high during the change of direction. These results suggest that experience can modify the postural stabilisation mechanisms during cutting, and prompt the lower limb muscle synergy to produce anticipatory adjustment to improve postural stability in the anterior-posterior and internal-external directions.